2015
DOI: 10.1556/mental.15.2014.004
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between alexithymia and hypnotic susceptibility: A review of the literature

Abstract: Elméleti háttér: Számos klinikai megfigyelés és kutatási eredmény utal rá, hogy a hipnózis iránti fogékonyság és az alexitímia hátterében közös -részben azonos, részben ellentétes irányban ható -mechanizmusok mûködnek. Ennek ellenére csak néhány tanulmány talál-ható a szakirodalomban, ami közvetlenül a két konstruktum kapcsolatával foglalkozik. Úgy tûnik, hogy a disszociatív hajlam, a fantáziakészség, az empátia és a mások érzelmei-nek azonosítására való képesség mind a hipnábilitás, mind az alexitímia szempon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…These findings were supported by our own research on perceived parental rearing style and hypnotizability (Költő, 2008;Költő & Bányai, 2008) and will be supplemented by further empirical evidence in the present thesis. In line with the social cognitive theories, we have found that hypnotic response is also influenced by contextual factors like time, setting (group versus individual) (Költő, Gősi-Greguss, et al, 2014), or the gender of the hypnotist (Költő, 2012).…”
Section: Hypnotizabilitysupporting
confidence: 82%
See 1 more Smart Citation
“…These findings were supported by our own research on perceived parental rearing style and hypnotizability (Költő, 2008;Költő & Bányai, 2008) and will be supplemented by further empirical evidence in the present thesis. In line with the social cognitive theories, we have found that hypnotic response is also influenced by contextual factors like time, setting (group versus individual) (Költő, Gősi-Greguss, et al, 2014), or the gender of the hypnotist (Költő, 2012).…”
Section: Hypnotizabilitysupporting
confidence: 82%
“…The perceived authority of the H may influence the subjects' emotional involvement in the hypnosis, even in standard laboratory hypnosis sessions (Bányai, Varga, & Gősi-Greguss, 2001). In an earlier phase of the present study it was demonstrated that female Hs evoked more positive and less negative emotions in their subjects (although the behavioral hypnotizability scores did not differ); still, there was a small but significant gender interaction (gender of the S × gender of the H) in HGSHS:A observer-scores (Költő, 2012). Hypnotists seem to be more hypnotizable than the general population (Gősi- Greguss, Bányai, & Varga, 1996), although their hypnotizability is not related to the perceived harmony of their interaction as either they or their Ss experience it in hypnosis (Varga, Józsa, Bányai, & Gősi-Greguss, 2012).…”
Section: Experimenter Effectsmentioning
confidence: 42%